Normative data for the anthropometric hand dimensions of the Mexican population - Rodríguez-Vega, Graciela; Rodríguez-Vega, Dora Aydee (European Public & Social Innovation Review, 2024)
Work-related musculoskeletal disorders are major occupational health risks that can be positively influenced by appropriate machine, tool, and workstation designs. Despite their importance in ergonomics, normative data for hand anthropometric dimensions have rarely been studied. This study aims to develop normative data for the Mexican population, analyze gender differences, and compare the data with those from other countries. Methodology: A survey of hand anthropometry in the Mexican population was conducted (2,275 males and 562 females). Four dominant hand dimensions were measured: hand length and breadth, palm length, and handgrip diameter. Results: We have presented descriptive statistics in this study (mean, standard deviation, and 5, 50, 95 percentiles). The results indicated significant differences between the sexes within the Mexican population for all hand dimensions. Discussion: significant differences were observed in data from other countries (mainly Asian countries), even with Latin American and Mexican (old surveys) populations. All data developed represent the Mexican population. There is no evidence of the development of similar data including a wide age range, both genders and big data sample. Conclusions: The presented data can be used to design hand tools, machinery, products, and workstations.